Lactic acid production by Lactobacillus casei using a sequence of seasonally available fruit wastes as sustainable carbon sources - Costa, Stefania; Summa, Daniela; Radice, Matteo; Vertuani, Silvia; Manfredini, Stefano; Tamburini, Elena (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Lactic acid (LA) production from fossil resources is unsustainable owing to their depletion and environmental concerns. Thus, this study aimed to optimize the production of LA by Lactobacillus casei in a cultured medium containing fruit wastes (FWs) from agro-industries and second cheese whey (SCW) from dairy production, supplemented with maize steep liquor (MSL, 10% v/v) as the nitrogen source. Methods: The FWs were selected based on seasonal availability [early summer (early ripening peach), full summer (melon), late summer (pear), and early autumn (apple)] and SCW as annual waste. Small-scale preliminary tests as well as controlled fermenter experiments were performed to demonstrate the potential of using various food wastes as substrates for LA fermentation, except for apple pomace. Results and discussion: A 5-cycle repeated batch fermentation was conducted to optimize waste utilization and production, resulting in a total of 180.56 g/L of LA with a volumetric productivity of 0.88 g/L∙h. Subsequently, mechanical filtration and enzymatic hydrolysis were attempted. The total amount of LA produced in the 5-cycle repeated batch process was 397.1 g/L over 288 h, achieving a volumetric productivity of 1.32 g/L∙h. These findings suggest a promising biorefinery process for low-cost LA production from agri-food wastes.